Hetero-deformation promoted strengthening and toughening in BCC rich eutectic and near eutectic high entropy alloys. (20th May 2023) - Chung, D.H.; Lee, J.; He, Q.F.; Kim, Y.K.; Lim, K.R.; Kim, H.S.; Yang, Y.; Na, Y.S.
Highlights: A series of eutectic and off-eutectic high entropy alloy were developed. The fully eutectic Al18 Co30 Cr11 Fe11 Ni30 showed exceptional strength-toughness combination. Hetero-Deformation induced strengthening and toughening is the crucial factor that enables this synergic effect. Abstract: Heterostructured eutectic high-entropy alloys (EHEAs) have attracted significant attention owing to their novel properties, such as balanced combinations of strength and fracture toughness. However, the toughening/strengthening mechanisms of these EHEAs have not been thoroughly investigated. In this study, we developed a series of dual-phase Al(18–2 x ) Co30 Cr(11+ x ) Fe(11+ x ) Ni30 ( x = -1, 0, 1) eutectic and near-eutectic HEAs containing face-centered cubic (FCC) and body-centered cubic (BCC) phases. Despite the high amount of BCC, which is referred to as the brittle phase, newly developed EHEAs exhibited superior fracture toughness. Interestingly, we discovered that a fully eutectic HEA exhibited further improvements in both yield stress and fracture toughness, outperforming our off-eutectic and other previously reported HEAs. By combining experiments and theoretical models, we demonstrated that the synergistic increase in both strength and toughness in our fully eutectic HEA was derived from the high hetero-deformation-induced (HDI) strengthening/toughening associated with a high misorientation angle at the grain/phase boundaries.